2008
DOI: 10.1093/bja/aen146
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and related techniques for postoperative pain: a systematic review of randomized controlled trials

Abstract: Postoperative pain management remains a significant challenge for all healthcare providers. The objective of this systematic review was to quantitatively evaluate the efficacy of acupuncture and related techniques as adjunct analgesics for acute postoperative pain management. We searched the databases of Medline (1966-2007), CINAHL, The Cochrane Central Register of Controlled Trials (2006), and Scopus for randomized controlled trials (RCTs) using acupuncture for postoperative pain management. We extracted data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(158 citation statements)
references
References 41 publications
(45 reference statements)
1
142
0
12
Order By: Relevance
“…Several studies have shown reduced opioid consumption and side effects (e.g., PONV, urinary retention) when acupuncture is used as part of multimodal postoperative analgesia, 86 although clinical opinion on its efficacy remains divided. 87 Considerable clinical heterogeneity remains between studies; for instance, some studies use penetrating needles as the sham intervention, which has been proposed to have a physiological effect.…”
Section: Acupuncturementioning
confidence: 99%
“…Several studies have shown reduced opioid consumption and side effects (e.g., PONV, urinary retention) when acupuncture is used as part of multimodal postoperative analgesia, 86 although clinical opinion on its efficacy remains divided. 87 Considerable clinical heterogeneity remains between studies; for instance, some studies use penetrating needles as the sham intervention, which has been proposed to have a physiological effect.…”
Section: Acupuncturementioning
confidence: 99%
“…Számos kutatás alapján néhány komplementer és alterna tív gyógymód az EBM kritériumai szerint is hatékony lehet, akár a perioperatív időszakban is. A hagyományos kínai orvoslás módszereit (akupunktúra, akupresszúra, fülakupunktúra) jó szorongásoldónak találták [37], hasznosak lehetnek intra és posztoperatív fájdalomcsil lapítás szempontjából [38][39][40], eredményesen megelőz hető és kezelhető e módszerekkel a posztoperatív hány inger és hányás [41]. A homeopátiás szereket több tanulmány vizsgálta, elsősorban ortopédiai műtétek utá ni fájdalomcsillapítás szempontjából, ám nem találták a készítményeket effektív analgetikumnak, bár a posztope ratív duzzanatot csökkenthetik [42,43].…”
Section: Az Egyes Gyógymódok Megítéléseunclassified
“…A systematic review reported that acupuncture and related techniques may be a useful adjunct analgesic for acute postoperative pain (SUN et al, 2008). One of the most studied effect of AP is analgesia, produced by the stimulation of certain acupoints (CASSU et al, 2008;LUNA, 2002;TEIXEIRA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%